Semiotic Analysis in the Lyrics of the Song Tikus-Tikus Kantor and Its Significance for Fraud Accounting Actors - Ardimansyah; Rafles Ginting; Elga Yulindisti; Anton Robiansyah; Rissa Anandita (Jurnal Sastra Indonesia, 2024)
The role of the song "Tikus-Tikus Kantor" by Iwan Fals serves as a metaphor for depicting workplace fraud, particularly in the context of company financial reporting. This study aims to empirically examine the song's meaning using semiotic analysis. The qualitative research method used Roland Barthes' semiotic approach to explore both denotative and connotative meanings within the song's lyrics. Symbols such as rats and cats represent actors in accounting fraud, namely perpetrators and auditors. The connotations within the lyrics depict rationalization, pressure, and competence, aligning with the Fraud Pentagon theory, which identifies triggering factors for fraud. The moral message in the song serves as a reminder for auditors to execute their duties with integrity and professionalism. From a dramaturgical perspective, the song highlights the relationship between fraud perpetrators and auditors, portraying the former as cunning rats and hungry cats. The research illustrates how fraud perpetrators can exploit the lack of attention or errors on the part of auditors. The moral message in the lyrics encourages auditors to enhance vigilance and integrity when examining financial reports. Consequently, this study provides theoretical contributions by applying semiotic analysis to understand the meaning of songs related to accounting fraud. The findings can serve as a basis for formulating policies to prevent accounting fraud for stakeholders.